2020
DOI: 10.1126/sciadv.aax0021
|View full text |Cite
|
Sign up to set email alerts
|

Deficient histone H3 propionylation by BRPF1-KAT6 complexes in neurodevelopmental disorders and cancer

Abstract: Lysine acetyltransferase 6A (KAT6A) and its paralog KAT6B form stoichiometric complexes with bromodomain- and PHD finger-containing protein 1 (BRPF1) for acetylation of histone H3 at lysine 23 (H3K23). We report that these complexes also catalyze H3K23 propionylation in vitro and in vivo. Immunofluorescence microscopy and ATAC-See revealed the association of this modification with active chromatin. Brpf1 deletion obliterates the acylation in mouse embryos and fibroblasts. Moreover, we identify BRPF1 variants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 61 publications
2
90
0
1
Order By: Relevance
“…H3K23pr was also recently identified. Of note, cardiac anomalies are present in a subset of patients with deficient H3K23pr catalyzed by BRPF1-KAT6 complexes [98]. Therefore, histone propionylation may critically contribute to cardiovascular homeostasis and diseases.…”
Section: Propionate and Propionylationmentioning
confidence: 99%
“…H3K23pr was also recently identified. Of note, cardiac anomalies are present in a subset of patients with deficient H3K23pr catalyzed by BRPF1-KAT6 complexes [98]. Therefore, histone propionylation may critically contribute to cardiovascular homeostasis and diseases.…”
Section: Propionate and Propionylationmentioning
confidence: 99%
“…BRPF1 encodes a component of the MOZ/MORF which has a histone H3 acetyltransferase activity. The frameshift variant we detected should alter the interaction with KAT6A and KAT6B thus impairing BRPF1 in activating KAT6A for H3K23 propionylation, as demonstrated for IDDDFP patients with variants comparable to that of patient 22 (Yan 2020). Not by chance, de novo truncating mutations in KAT6B, which cause a spectrum of disorders, include, although rarely, C1M (Kennedy 2019), and more frequently craniosynostosis which in turn may cause Chiari malformation (Bashir 2017).…”
Section: W3 Histone Acetyltransferasesmentioning
confidence: 66%
“…Many members of the family Lachnospiraceae are known as butyrate-producing bacteria (30,31). A previous study revealed that butyrate alleviated the acylation deficiency (caused by the mutations of in the bromodomain-and PHD finger-containing protein 1 Brpf1 gene) of histone H3 at lysine 23 in mouse embryos and fibroblasts and human embryonic kidney 293 cells, and this deficiency was also found in children with neurodevelopmental delay (32). This study suggests that butyrate may alleviate the severity of neurodevelopmental delay in children.…”
Section: Discussionmentioning
confidence: 98%